Inverse scattering problem for nonstationary Dirac-type systems on the plane - Ismailov, Mansur I. (Academic Press Inc Elsevier Science, 2010)
In this paper the forward and inverse scattering problems for the nonstationary Dirac-type systems on the plane are considered. The scattering data for the inverse scattering problem (ISP) is defined and a unique restoration of the potential from the scattering data is proved. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Nonstationary scattering problem; Dirac-type system; Inverse problem on the plane